1999
DOI: 10.1038/sj.onc.1202470
|View full text |Cite
|
Sign up to set email alerts
|

The translation initiation factor, hu-Sui1 may be a target of hepatitis B X antigen in hepatocarcinogenesis

Abstract: The role of hepatitis B virus X antigen in the development of hepatocellular carcinoma was explored by stably transfecting HepG2 cells with an X antigen expression vector, and identifying the dierences in gene expression that distinguish X positive from X negative cells by subtractive PCR. One dierentially expressed gene, the human homolog of sui1 (hu-sui1), encodes a translation initiation factor whose expression was suppressed by X antigen in HepG2 cells. Hu-Sui1 was also expressed in nontumor liver but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 69 publications
2
100
0
Order By: Relevance
“…HBxAg may do this by activating signal transduction pathways and by binding to transcription factors that influence host gene expression (Henkler and Koshy, 1996;Feitelson and Duan, 1997). Among these changes, HBxAg upregulates the expression of cellular proteins that promote cell growth and survival (Su et al, 1994;Terradillos et al, 1997), and suppresses expression or functionally inactivates negative growth regulatory proteins (Wang et al, 1994;Truant et al, 1995;Sun et al, 1998;Feitelson et al, 1999;Lian et al, 1999;Kondoh et al, 2001). Although HBxAg is expressed in the liver throughout chronic infection (Wang et al, 1991), it is not clear whether HBxAg downregulates the expression of some of these pathways by epigenetic mechanisms, such as DNA methylation (Kanai et al, 1997(Kanai et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…HBxAg may do this by activating signal transduction pathways and by binding to transcription factors that influence host gene expression (Henkler and Koshy, 1996;Feitelson and Duan, 1997). Among these changes, HBxAg upregulates the expression of cellular proteins that promote cell growth and survival (Su et al, 1994;Terradillos et al, 1997), and suppresses expression or functionally inactivates negative growth regulatory proteins (Wang et al, 1994;Truant et al, 1995;Sun et al, 1998;Feitelson et al, 1999;Lian et al, 1999;Kondoh et al, 2001). Although HBxAg is expressed in the liver throughout chronic infection (Wang et al, 1991), it is not clear whether HBxAg downregulates the expression of some of these pathways by epigenetic mechanisms, such as DNA methylation (Kanai et al, 1997(Kanai et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In general apoptosis can occur in the absence of de novo proteins synthesis. However, depending on the stimulus and cell type, the ongoing protein synthesis may also be required for apoptosis to occur Figure 6 Genotoxic and endoplasmic reticulum stress may control translation initiation ®delity by upregulating the levels of eIF1 A121/SUI1 patients suering from hepatocellular carcinoma revealed the absence of eIF1 A121/SUI1 gene expression only in the hepatic tumors but not in the matching normal hepatic tissues (Lian et al, 1999). It is interesting that a variety of RNA viruses can synthesize multiple proteins from a single transcript by ribosomal frameshifting (Cui et al, 1998 and references therein).…”
Section: Regulation Of Eif1 A121/sui1mentioning
confidence: 99%
“…For example, when overexpressed, eIF1 A121/SUI1 inhibits the colony forming eciency of human cancer cells (Lian et al, 1999 and our unpublished results). Recently, it has been shown that the hepatitis B virus X antigen can downregulate the expression of eIF1 A121/SUI1 (Lian et al, 1999). Analyses of tumors and matching normal tissues from HBV-infected Figure 5 Stress-induced apoptosis may involve activation of caspase cascade; caspases can cleave cellular proteins that control basic cellular processes including replication, transcription and building of cellular architecture.…”
Section: Regulation Of Eif1 A121/sui1mentioning
confidence: 99%
“…Finally, R-Ras is a ras oncogene member that is implicated in immortalization and transformation of normal cells to malignancy. Additionally, two tumor suppressor genes, BARD1 and SUI 1, are down regulated, of which BARD 1 is implicated in BRCA1-mediated tumor suppression [20], while SUI 1 encodes a translation initiation factor that is suppressed during tumorigenesis [21]. This unique combination of up regulation of five potent oncogenes (Hoxa9/ N-MYC/Koc1/BMI1/R-Ras) and down regulation of two tumor suppressors (BARD1/SUI1) appear to be the molecular basis of rapid progression from MDS to AML in this patient.…”
Section: Discussionmentioning
confidence: 99%